2020
DOI: 10.1016/j.jstrokecerebrovasdis.2020.104881
|View full text |Cite
|
Sign up to set email alerts
|

Acute Stroke Care in the Coronavirus Disease 2019 Pandemic

Abstract: Coronavirus disease 2019 (COVID-19) is a pandemic respiratory disease with serious public health risk and has taken the world off-guard with its rapid spread. As the COVID-19 pandemic intensifies, overwhelming the healthcare system and the medical community, current practice for the management of acute ischemic stroke (AIS) will require modification, and guidelines should be relaxed while maintaining high standard quality of care. The aim of these suggestions is to avoid contributing to the rapid spread of COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
93
0
17

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(116 citation statements)
references
References 15 publications
0
93
0
17
Order By: Relevance
“…However, given that stroke thrombectomies must be done emergently due to the time-sensitive nature of cerebral ischemia, patients should be assumed to be COVID-19 positive and only essential personnel should be present in the angiography suite [ 13 ]. Others have recommended consolidating imaging studies to minimize staff exposure [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, given that stroke thrombectomies must be done emergently due to the time-sensitive nature of cerebral ischemia, patients should be assumed to be COVID-19 positive and only essential personnel should be present in the angiography suite [ 13 ]. Others have recommended consolidating imaging studies to minimize staff exposure [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…16 Defined and designated areas for all stroke patients and screening by an emergency room physician for suspected COVID-19 symptoms, with full protective gear (full-sleeved gown, surgical mask, eye protection (face shield and/or goggles), gloves, and head cover), have been proposed. 17 Since testing currently does not include a point-of-care device, universal precautions to healthcare workers become even more crucial.…”
Section: Acute Stroke Carementioning
confidence: 99%
“…Last, studies showed that SARS-CoV-2 invades human respiratory epithelial cells through its S-proteins and angiotensin-converting enzyme 2 (ACE2) receptors on human cells surface [7,25]. The expression and function of ACE2 receptor, normally reduced in hypertensive patients, is further reduced during SARS-CoV2 infection leading to a lower ability on controlling blood pressure [26].…”
Section: Covid-19 and Cerebrovascular Diseasesmentioning
confidence: 99%